Pengaruh Pemberian Pupuk Organik Cair Hasil Proses Pencernaan Anaerobik Limbah Industri Nata De Coco dan Kotoran Sapi terhadap Sifat Kimia Tanah pada Media Tanam Selada - Zaitun Zaitun; M. Sri Saeni; M. Kooswardhono; H.M.H. Bintoro Djoefri (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
Effect of Liquid Organic Fertilizer from Nata de coco Waste and Cow Manure in Anaerobic Digester Processing Application in Soil Chemistry Properties of Lettuce PlantingABSTRACT. The objective of this experiment was to study effect of liquid organic fertilizer from nata de coco waste and cow manure in anaerobic digester processing application in soil chemistry properties of lettuce planting. The experiment is conducted at Physical Chemistry and Environmental Laboratory of IPB and in Jabon Mekar Village, Parung, West Java. The treatment of this experiment is application of liquid fertilizer (organic fertilizer) once, twice, and three time a week from effluent anaerobic digester 75% nata de coco waste + 25% cow manure, 50% nata de coco waste + 50% cow manure, 25% nata de coco waste + 75% cow manure, and 100% cow manure compared with control (inorganic fertilizer) on lettuce. The result showed that the application of liquid organic fertilizer from nata de coco waste and cow manure in anaerobic digester processing can increase the soil chemistry properties.